Paleoenvironments of the evolving P liocene to early P leistocene foreland basin in northwestern T aiwan: An example from the D ahan R iver section - Tsun‐You Pan; Andrew Tien‐Shun Lin; Wen‐Rong Chi (Island Arc, 2015)
The overriding of the L uzon volcanic arc atop the underlying C hinese rifted‐continental margin has caused the formation of the T aiwan mountain belts and a peripheral foreland basin west of the orogen since the late Miocene. In this study, lithofacies analysis and calcareous nannofossil biostratigraphic investigations of the Dahan River section in northwestern ( NW ) T aiwan were performed. Our results offer insights into the temporal evolution of the sedimentary environments and the competing effects of the sedimentation and basin tectonics of the NW T aiwan foreland basin from the P liocene to early P leistocene. Nannofossil biostratigraphic studies showed that the upper K ueichulin F ormation and the overlying C hinshui S hale can be assigned to the NN 15 biozone of the P liocene age, and the C holan F ormation pertains to NN 16– NN 18 of the early P leistocene. The NN 15– NN 16 boundary coincides roughly with the boundary of the C hinshui S hale and C holan F ormation. We recognized three major sedimentary environments in the studied foreland succession comprising the upper K ueichulin F ormation, C hinshui S hale, C holan F ormation and Y angmei F ormation, in ascending order. During the deposition of the upper K ueichulin Formation in the early P liocene, the dominant environment was a wave‐ and tide‐influenced open marine setting. During the late P liocene, the environment deepened to an outer‐offshore setting when the sediments of C hinshui Shale were accumulated. In the P leistocene, the environment then shallowed to wave‐dominated estuaries during the deposition of the lower C holan F ormation, and the basin was rapidly filled, generating a meandering and sandy braided river environment during the deposition of the upper C holan to the Y angmei Formation. In summary, the evolution of sedimentary environments in the studied succession shows a deepening then a shallowing and coarsening upward trend during the period from the Pliocene to the Pleistocene, spanning the age from approximately 4 to 1 Ma.